Co-O-Ce sites on defect-engineered Co0.05Ce0.95O2-δ solid solutions drive the direct conversion of CO2 to dimethyl carbonate - Yunhui Xia; Bingyan Liu; Mingyuan Zhang; Guohui Cai; Mengjia Zhang; Jianghui Lin; Ling Li (Chemical Engineering Journal, 2026)

From structural features to mouse acute intraperitoneal toxicity prediction: a triple computational toxicology approach for safety assessment of flavonoids - Yichen Yang; Na Zhang; Ting Ren; Lijiao Zhao; Rugang Zhong; Ning Lin; Guohui Sun (Molecular Diversity, 2026)

17β-Estradiol alleviates cognitive deficits by modulating fear memory reconsolidation in a PTSD rat model - Han Wang; Han Lin; Zilong Zhong; Baoying Jiang; Siyi Li; Jiahao Tang; Xiaoping Zhou; Guohui Zhu; Yang Liu; Wenhao Han; Jinhua Dou; Lin Sun (Psychopharmacology, 2026)

Disentangling seasonal dynamics and transboundary transport of PAHs in a coastal monsoon city - Haolong Zhang; Zheng Zhang; Wenhui Lin; Guohui Lin; Cheng Luo; Ting Fang; Nemin Luo; Minggang Cai; Lei Wang; Bin Yan; Yan Lin (Atmospheric Research, 2026)

Chitosan-based coatings and films: Mechanisms and applications in postharvest preservation of mangoes - Guohui Yi; Simin Fan; Huanqi Wu; Ajahar Khan; Ruchir Priyadarshi; Wanying Sun; Derong Lin; Yiqin Zhang (Food Packaging and Shelf Life, 2025)

Performance of adjacent metro tunnels during deep excavation: A case study in Hangzhou - Zhaorui Lin; Yalong Jiang; Changjie Xu; Minliang Chi; Tao Fang; Lingxiao Guan; Guohui Feng; Gang Lin (Transportation Geotechnics, 2025)

Assessment of the rat acute oral toxicity of quinoline-based pharmaceutical scaffold molecules using QSTR, q-RASTR and machine learning methods - Jianing Xu; Ting Ren; Feifan Li; Shuo Chen; Tengjiao Fan; Lijiao Zhao; Rugang Zhong; Guohui Sun; Ning Lin (Molecular Diversity, 2025)

Fusion of monocular camera and 3D LiDAR data for navigation line extraction under corn canopy - Chao Ban; Lin Wang; Tong Su; Ruijuan Chi; Guohui Fu (Computers and Electronics in Agriculture, 2025)

Low-frequency ultrasound-driven piezoelectric films repair neuro-immune circuits in diabetic wound healing - Chenyan Yu; Ying Hu; Xin Zhang; Kaixu Yu; Lang Chen; Wenqian Zhang; Shengming Zhang; Zhenhe Zhang; Ruiyin Zeng; Yuheng Liao; Yanzhi Zhao; Lin Gan; et al. (Chemical Engineering Journal, 2025)

Energy-efficient task scheduling with binary random faults in cloud computing environments - Lei Jin; Jie Yuan; Dequn Zhou; Xiuzhi Sang; Shi Chen; Xianyu Yu; Guohui Lin (Swarm and Evolutionary Computation, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Sodium hydrosulfide application induces chilling tolerance in banana fruits by enhancing antioxidant gene expression through the upregulation of the ethylene response factors MaERF53L/121L - Zengxiang Lin; Wei Wei; Danling Cai; Wei Shan; Jianye Chen; Yingying Yang; Jia Si; Wangjin Lu; Guohui Zhu; Chaojie Wu; Jianfei Kuang (Food Chemistry, 2025)

The zinc-finger transcription factor ZFP8 negatively regulates the drought stress response in Arabidopsis thaliana by inhibiting the transcriptional activity of ABF2 - Yu'ang Tian; Yanling Li; Kelan Wang; Ran Xia; Yingru Lin; Guohui Pan; Haoyu Shi; Dawei Zhang; Honghui Lin (Journal of Plant Physiology, 2024)

Native CRISPR-Cas-based programmable multiplex gene repression in Klebsiella variicola - Zhifeng Mo; Siying Lin; Ting Li; Guohui Yu; Yunhao Sun; Jianuan Zhou; Zeling Xu (Biotechnology Letters, 2024)

Storm Liquefaction Deposits: A Possibility of Time Reversal in Sedimentary Strata of an Estuarial Coastal Area - Guohui Xu; Yupeng Ren; Guanghai Hu; Zhiqin Liu; Yongfu Sun; Lin Lin (Journal of Ocean University of China, 2024)

Fully Coupled Hydrodynamic–Mooring–Motion Response Model for Semi-Submersible Tidal Stream Turbine Based on Actuation Line Method - Guohui Wang; Jisheng Zhang; Xiangfeng Lin; Hao Chen; Fangyu Wang; Siyuan Liu (Journal of Marine Science and Engineering, 2024)
The modeling of floating tidal stream energy turbine (FTSET) systems demands significant computational resources, especially when incorporating fully coupled models that integrate hydrodynamics, mooring, motion response, and their interactions. In this study, a novel hybrid numerical model for FTSET systems has been developed, utilizing the open-source software OpenFOAM. The hydrodynamic characteristics of three-bladed vertical-axis turbines are simulated in steady, three-dimensional wave–current numerical tanks using an unsteady actuator line method (UALM). The interFoam two-phase Navier–Stokes solver within OpenFOAM is utilized to manage the kinematic characteristics of the floating platform. Mooring dynamics are addressed using the mass–spring–damper model (MoorDyn), and turbine wake dynamics are resolved using a buoyancy-modified RANS turbulence model. The comprehensive model can simulate wave, flow, mooring dynamics, platform motion, and the interactions between the turbine and platform within FTSET systems. To validate the model, several scenarios are analyzed, and experiments are conducted to validate the numerical results. The model accurately predicts platform motion responses and mooring line tensions, especially under wave–current conditions, capturing the interconnected effects of platform motion during turbine rotation. Additionally, the model extends predictions of turbine–platform wake development and interaction.

Co-exposure to fluoride and sulfur dioxide induces abnormal enamel mineralization in rats via the FGF9-mediated MAPK signaling pathway - Ying Lv; Jin Yao; Yang Wang; Guohui Bai; Changhu Lin; Chenglong Tu (Environmental Research, 2024)

Variability in molecular composition and optical absorption of atmospheric brown carbon aerosols in two contrasting urban areas of China - Yue Lin; Yuemei Han; Guohui Li; Lijuan Li; Xin Zhang; Junji Cao (Science of The Total Environment, 2024)

Experimental investigation of motion response and mooring load of semi-submersible tidal stream energy turbine under wave-current interactions - Guohui Wang; Jisheng Zhang; Bohua Lu; Xiangfeng Lin; Fangyu Wang; Siyuan Liu (Ocean Engineering, 2024)

Catalytic hydrodeoxygenation of 5-hydroxymethylfurfural to 2,5-dimethylfuran over Pd-Co bimetallic catalysts supported on MoCx - Yu Chen; Haoquan Guo; Junye Yang; Kaiyang Xu; Xinyu Lu; Yue Yang; Hongqiao Lin; Lizhi Wu; Li Tan; Guohui Yang; Noritatsu Tsubaki; Xiaoli Gu; et al. (Fuel, 2024)

Bavachin combined with epimedin B induce idiosyncratic liver injury under immunological stress conditions - Mengmeng Lin; Yingying Li; Bo Cao; Jing Xu; Yujun Zhang; Guohui Li; Xiaohe Xiao; Chunyu Li (Chemico-Biological Interactions, 2023)

Adjusting spatial use to establish productive and stable Elymus nutans monocultures and mixed sowing systems - Wen Ren; Zhixin Zhang; Yuying Shen; Changing Lin; Xianlong Yang; Guohui Wang; Kun Yang; Mazuoma Mi; Ye Liu; Hui Wang (Field Crops Research, 2023)

Experimental investigation of wake and thrust characteristics of a small-scale tidal stream turbine array - Jisheng Zhang; Guohui Wang; Xiangfeng Lin; Yudi Zhou; Risheng Wang; Hao Chen (Ocean Engineering, 2023)

Intensity-dependent mass search for improving metabolite database matches in chemical isotope labeling LC-QTOF-MS-based metabolomics - Yunong Li; Hao Li; Taibo Luo; Guohui Lin; Liang Li (Analytica Chimica Acta, 2023)

Sodium Fluoride and Sulfur Dioxide Derivatives Induce TGF-β1-Mediated NBCe1 Downregulation Causing Acid–Base Disorder of LS8 Cells - Ying Lv; Wentai Wang; Lili Yao; Jiaojiao He; Guohui Bai; Changhu Lin; Chenglong Tu (Biological Trace Element Research, 2023)

Comprehensive identification of protein orthologs in the family Ascoviridae facilitates an understanding of phylogenomics, protein conservation, and phosphorylation - Yanhua Shi; Weiping Lin; Jinxin Chu; Guohui Wang; Punan Zhao; Guo-hua Huang; Dianhai Hou (Archives of Virology, 2022)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Family-1 UDP glycosyltransferases in pear (Pyrus bretschneideri): Molecular identification, phylogenomic characterization and expression profiling during stone cell formation - Xi Cheng; Abdullah Muhammad; Guohui Li; Jingyun Zhang; Jun Cheng; Jingxiang Qiu; Taoshan Jiang; Qing Jin; Yongping Cai; Yi Lin (Molecular Biology Reports, 2019)

N2O emission characteristics and its affecting factors in rain-fed potato fields in Wuchuan County, China - Liwei Wang; Cheng Wang; Zhihua Pan; Hui Xu; Lin Gao; Peiyi Zhao; Zhiqiang Dong; Jingting Zhang; Guohui Cui; Sen Wang; Guolin Han; hui Zhao (International Journal of Biometeorology, 2017)

Comparison of coral diversity between big and small atolls: a case study of Yongle atoll and Lingyang reef, Xisha Islands, central of South China Sea - Meixia Zhao; Kefu Yu; Qi Shi; Hongqiang Yang; Bernhard Riegl; Qiaomin Zhang; Hongqiang Yan; Tianran Chen; Guohui Liu; Ziyun Lin (Biodiversity and Conservation, 2017)

Genes in the serotonin pathway are associated with bipolar affective disorder in a Han Chinese population - Bo Xiang; Zhenxing Yang; Yin Lin; Lijie Guan; Xuan Li; Wei Deng; Zeyu Jiang; Guohui Lao; Qiang Wang; Xiaoyu Hao; Xiang Liu; Yingcheng Wang; et al. (Neuroscience Bulletin, 2014)

Subtype identification of the novel A H1N1 and other human influenza A viruses using an oligonucleotide microarray - Xiaoping Kang; Yongqiang Li; Honghe Sun; Weili Wu; Hong Liu; Fang Lin; Chenfeng Qing; Guohui Chang; Qingyu Zhu; Weijun Chen; Yinhui Yang (Archives of Virology, 2010)